A SCIENTOMETRIC ANALYSIS OF HEALTH AND POPULATION RESEARCH IN SOUTH ASIA: FOCUS ON TWO RESEARCH ORGANIZATIONS - Mahbuba, Dilruba; Rousseau, Ronald; Srivastava, Divya (Malaysian Journal of Library and Information Science, 2010)
In this article we provide a scientometric comparison between two health and population research organizations, namely the International Centre for Diarrhoeal Disease Research in Bangladesh (ICDDR,B) and the National Institute of Cholera and Enteric Diseases (NICED) in India, during the period 1979-2008. We study these two institutes because they conduct similar research and because of their collaboration ties. Data are collected from the Web of Science (WoS) as well as from official records of these two organizations. The analysis presents the evolution of publication activities. Special attention is given to research impact through time series of the institutional h- and R-indices, as well as to the trend in yearly citations received. Types of publications, international collaboration with other countries, top scientists and most cited articles co-authored by scientists from these institutions are highlighted. It is observed that female scientists play a minor role in these two institutes.